The Influence of Project-Based Learning Model on Self-Efficacy in Speaking: A Quasi-Experimental Study in Indonesian Language Learning - Muhammad Akir; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
Speaking ability is one of the essential skills in learning the Indonesian language, particularly at the elementary school level. However, observations at SD Negeri 083 Pidoli revealed that sixth-grade students still have low self-efficacy in speaking. They tend to be passive, hesitant to express their opinions. This condition is exacerbated by the continued use of conventional teaching methods. Therefore, an instructional model that promotes active student participation and boosts their speaking confidence is necessary. One model considered effective in this context is Project Based Learning (PjBL). This study aims to examine the influence of the PjBL model on students’ speaking self-efficacy in the Indonesian language subject for sixth-grade students at SD Negeri 083 Pidoli, Mandailing Natal Regency, during the 2025–2026 academic year. The study employed a quantitative approach using a one-group pretest-posttest design. The research subjects consisted of 20 students. Instruments used included a self-efficacy questionnaire, observation sheets for student and teacher activities, and a speaking skills test. The results indicated a significant improvement in students’ self-efficacy after the implementation of the PjBL model. The average pretest score of 67.4 increased to 89.8 in the posttest. The percentage of students achieving mastery learning rose from 50% to 100%. The self-efficacy category also shifted, with 50% of students initially in the